Quantifying the intangible impact of the Olympics using subjective well-being data - Dolan, P.; Kavetsos, G.; Krekel, C.; Mavridis, D.; Metcalfe, R.; Senik, C.; Szymanski, S.; Ziebarth, N. R. (CEP Discussion Paper, 2019)
Hosting the Olympic Games costs billions of taxpayer dollars. Following a quasi-experimental setting, this paper assesses the intangible impact of the London 2012 Olympics, using a novel panel of 26,000 residents in London, Paris, and Berlin during the summers of 2011, 2012, and 2013. We show that hosting the Olympics increases subjective well-being of the host city's residents during the event, particularly around the times of the opening and closing ceremonies. However, we do not find much evidence for legacy effects. Estimating residents' implicit willingness-to-pay for the event, we do not find that it was worth it for London alone, but a modest wellbeing impact on the rest of the country would make hosting worth the costs.